Synthesis, Characterization, Antibacterial and Anti-Inflammatory Activities of Enoxacin Metal Complexes - Saeed Arayne; Najma Sultana; Urooj Haroon; M. Ahmed Mesaik (Bioinorganic Chemistry and Applications)
The present work comprises the synthesis of enoxacin (Heno) complexes with various transition metals. Two types of complexes [M(eno)2(H2O)2]3H2O(M=CuII, NiII or MnII) and [M(eno)(H2O)2]Cl⋅4H2O  (M=FeIII) were obtained. The complexes were characterized by different physicochemical, spectroscopic, and elemental analysis. Results suggest that enoxacin interacts with the metals as a monoanionic bidentate ligand. These complexes were also tested for their antibacterial activity against eleven (11) different microorganisms, and the results were compared with the parent drug. Moreover all the metal complexes were also tested for their ability to scavenge reactive oxygen species where by MnII and CuII complexes exhibited potential to mediate anti-inflammatory response.